Inteligencia emocional en padres de escolares de 8 a 12 años con problemas de comportamiento: revisión documental (2021)
Bibliographic review on the vision of different authors in everything related to behavioral problems and emotional intelligence in children aged 8 to 12 years; Highlighting the importance of emotional education. Behavioral problems are a problem currently present in the school context, which is why a primary intervention should be developed where the topic is prevention, which is based on emotional skills that allow avoiding the appearance of dysfunctional behaviors, outside of the appropriate ones. for this stage of evolutionary development in which the child is.